2019
DOI: 10.1002/cncr.31863
|View full text |Cite
|
Sign up to set email alerts
|

Beyond chemotherapy: Emerging biomarkers and therapies as small cell lung cancer enters the immune checkpoint era

Abstract: For decades, clinicians have witnessed no therapeutic advances for small cell lung cancer, including no US Food and Drug Administration‐approved targeted therapies; recently, immune‐checkpoint blockade has emerged as a promising new option for the treatment of patients with relapsed small cell lung cancer (including recent US Food and Drug Administration approval of nivolumab in the third‐line setting) and soon may represent the frontline standard of care in combination with chemotherapy. However, there is a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Small cell lung cancer (SCLC) is a malignant disease with a poor prognosis, with most patients being already in a metastatic stage at diagnosis. Current diagnostic methods rely on clinical imaging using computed tomography (CT) and positron emission tomography/CT in combination with cytological/histopathological biopsies of the tumor-suspected lesions of the lung [ 33 , 34 ] Few blood-based biomarkers have been clinically examined for diagnosis and screening [ [35] , [36] , [37] , [38] , [39] , [40] ]. Although the precise pathogenetic mechanisms of SCLC are not fully understood, several genetic mutations, protein and metabolic abnormalities have been identified.…”
Section: Special Issue On Clinical Metabolomicsmentioning
confidence: 99%
“…Small cell lung cancer (SCLC) is a malignant disease with a poor prognosis, with most patients being already in a metastatic stage at diagnosis. Current diagnostic methods rely on clinical imaging using computed tomography (CT) and positron emission tomography/CT in combination with cytological/histopathological biopsies of the tumor-suspected lesions of the lung [ 33 , 34 ] Few blood-based biomarkers have been clinically examined for diagnosis and screening [ [35] , [36] , [37] , [38] , [39] , [40] ]. Although the precise pathogenetic mechanisms of SCLC are not fully understood, several genetic mutations, protein and metabolic abnormalities have been identified.…”
Section: Special Issue On Clinical Metabolomicsmentioning
confidence: 99%
“…Unlike NSCLC, the role of TMB in SCLC patients treated with immunotherapy is still unclear. Despite SCLC being characterized by a high somatic mutational burden [ 60 ], due to the strong association with smoking habit [ 61 , 62 ], the identification of predictors of SCLC response to ICIs remains challenging and the use of LB has been reported only in the phase III IMpower 133 trial of atezolizumab plus chemotherapy in patients with extensive-stage, treatment naïve SCLC [ 63 ]. Exploratory correlative bTMB study on 351 patients of the BEP group showed no correlation between bTMB and clinical benefit maybe due to the high myelosuppressive activity of the backbone chemotherapy, as speculated by the authors.…”
Section: Analysis Of Ctdna Profiling To Estimate Tmbmentioning
confidence: 99%
“…As the TME results from a very active dynamic of changes due to the continuous interactions between the host and genetically unstable cancer cells, it is important to consider in all studies the fourth dimension of time: TME is the result of an evolutionary process, particularly when immune editing is on-going as in the case of immune active cancer that are most likely to enable immune escape of prolific cancer cells that lose various types of requirements necessary for innate and adaptive immune recognition [30,[64][65][66][67][68][69][70].…”
Section: Genetics Determining Cancer Immune Phenotypesmentioning
confidence: 99%